2006
DOI: 10.1111/j.1574-6968.1997.tb12691.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for natural transformation of Bacillus subtilis in foodstuffs

Abstract: The effect of foodstuffs on the natural transformation of Bacillus subtilis was investigated. As examples of complex food matrices milk with various fat contents as well as chocolate milk were used. The frequencies of transformation varied with the fat content and ranged between 3.8 X 10(-4) and 1.4 X 10(-3). Highest frequencies of about 3 X 10(-3) were observed in chocolate milk with 1.5% fat. Development of competence was observed in chocolate milk, resulting in maximal transformation frequencies upon incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In the future more environmental compartments where gene transfer occurs will be identified. It is conceivable that Bräutigam et al, 1997;Davison, 1999;Day, 1998;Kay et al, 2002;Li et al, 2001;Lorenz and Wackernagel, 1994;Mercer et al, 2001;Schlimme et al, 1997;Stotzky et al, 1990. with improved experimental techniques gene transfer will be confirmed in very specific habitats where detection efforts have so far failed. For instance, it may be possible to identify natural transformation in the gastrointestinal tract, a habitat known to be rich in DNA degrading activity and probably not optimal for the development of DNA uptake competence of bacteria, but where high concentrations of bacteria are exposed to a variety of DNA molecules ingested with the food (Jonas et al, 2001).…”
Section: Microbial Horizontal Gene Transfer Processesmentioning
confidence: 95%
“…In the future more environmental compartments where gene transfer occurs will be identified. It is conceivable that Bräutigam et al, 1997;Davison, 1999;Day, 1998;Kay et al, 2002;Li et al, 2001;Lorenz and Wackernagel, 1994;Mercer et al, 2001;Schlimme et al, 1997;Stotzky et al, 1990. with improved experimental techniques gene transfer will be confirmed in very specific habitats where detection efforts have so far failed. For instance, it may be possible to identify natural transformation in the gastrointestinal tract, a habitat known to be rich in DNA degrading activity and probably not optimal for the development of DNA uptake competence of bacteria, but where high concentrations of bacteria are exposed to a variety of DNA molecules ingested with the food (Jonas et al, 2001).…”
Section: Microbial Horizontal Gene Transfer Processesmentioning
confidence: 95%
“…These results, and those obtained in challenge experiments performed to investigate the effect of added DNase I in sausages, indicate that the meat matrix had a protective effect on free plasmid DNA. Further information of DNA stability in milk was reported by Bräutigam et al [24], who showed that free bacterial DNA remained detectable for 12 days in ultra high temperature-treated milk stored at 4 °C whereas storage at 20 °C resulted in a rapid degradation within a few days.…”
Section: Dna Stabilitymentioning
confidence: 84%
“…Thus, environmental determinants are important factors affecting natural transformation. Natural transformation has been observed and thoroughly studied in a wide variety of bacterial species, including Streptococcus pneumoniae (S. pneumoniae) (Lefrancois et al, 1998;Johnsborg and Havarstein, 2009;Straume et al, 2015), Neisseria (Facius and Meyer, 1993;Hamilton and Dillard, 2006;Zhang et al, 2013), Bacillus subtilis (B. subtilis) (Kosovich and Prozorov, 1990;Brautigam et al, 1997;Le et al, 2017), Haemophilus influenzae (H. influenzae) (Redfield, 1993;Mell et al, 2011), Vibrio cholerae (V. cholerae) (Frischer et al, 1990;Watve et al, 2014;Dalia et al, 2017), and Acinetobacter baylyi (A. baylyi) (Vaneechoutte et al, 2006;Merod and Wuertz, 2014;Utnes et al, 2015;Hulter et al, 2017;Leong et al, 2017;Suarez et al, 2017;Nero et al, 2018;Mantilla-Calderon et al, 2019). Although most bacteria possess competence genes, numerous conditions or signals trigger competence and are often species specific (Seitz and Blokesch, 2013).…”
Section: Introductionmentioning
confidence: 99%